Modulation of fenestrated vasculature in the median eminence and area postrema in response to neurotoxin exposure and its impairment in aging - Pham, Viana Q.; Tutunculer, Melike; Al-Dulaimi, Halah; Ardjmand, Daniel; Fleischmann, William; Bachor, Tomas P.; Xu, Allison W. (Frontiers in Aging Neuroscience, 2025)
Effective communication between the brain and peripheral tissues is crucial for homeostasis and health, and its impairment is a defining feature of aging. Circumventricular organs, characterized by the presence of fenestrated capillaries and absence of a blood–brain barrier (BBB), play a crucial role in controlling substance exchange between the brain and the blood. To date, adaptive changes in fenestrated vasculature in response to environmental insults remain poorly understood. In this study, we show that fenestrated capillaries in the median eminence (ME) and area postrema (AP)—two distinct circumventricular organs critical for metabolic control—undergo differential remodeling when exposed to circulating monosodium glutamate (MSG), a BBB-impermeable neurotoxin. Upon MSG exposure, fenestrated capillaries and vascular permeability were decreased in the ME but increased in the AP, and these changes were closely associated with the expression of angiogenic factors pleiotrophin (Ptn) and vascular endothelial growth factor A (Vegfa). In both ME and AP, adult tanycytes expressed high levels of Ptn and have processes in close contact with fenestrated capillaries. Significantly, the adaptive regulation of Ptn expression and the ability to modulate fenestrated capillaries and vascular permeability were abolished in both ME and AP of aged animals. Together, our findings suggest that tanycytic expressions of the angiogenic factor PTN, in conjunction with VEGF, are differentially regulated in distinct circumventricular organs upon exposure to neurotoxins, leading to region-specific remodeling of fenestrated endothelium. Our study further demonstrates that the loss of plasticity in fenestrated vasculature may be a hallmark feature of brain aging.